PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KETERLIBATAN KEPUTUSAN PEMBELIAN DAN KEPERCAYAAN PADA KONSUMEN SHOPEE DI UNIVERSITAS SYIAH KUALA - Ria Amalia Fhonna, Sorayanti Utami (Departemen Manajemen, 2018)
Abstract: This study aims to measure the effect of Electronic Word of Mouth to Shopee’s consumer Purchase Decision involvement at Syiah Kuala University with Trust as mediating variable. The sample used in this study are Syiah Kuala University students who access Shopee application were 204 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Purposive Sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved.Based on the results of the HLM analysis indicated that Electronic Word of Mouth positively influence Purchase Decision Involvement, Electronic Word of Mouth positively influence Trust, Trust positively influence Purchase Decision Involvement and Trust mediate the relationship between Electronic Word of Mouth and Purchase Decision Involvement.